2011
DOI: 10.1002/hed.21451
|View full text |Cite
|
Sign up to set email alerts
|

Questionable necessity to remove the submandibular gland in neck dissection

Abstract: Saliva is of major importance in taste, speech, swallowing, and protection against dental caries. Neck dissection surgery and/or radiotherapy may impair the function of the submandibular glands. Over the years, there has been a trend toward more conservative approaches to neck dissection. Metastasis to the submandibular gland itself is extremely rare and if removal of the lymph nodes of sublevel IB is imperative, it seems feasible to preserve the submandibular gland, unless it is involved by direct tumor exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 80 publications
2
13
0
1
Order By: Relevance
“…Several prior reports have suggested the safety of submandibular gland preservation during treatment of head and neck carcinoma, citing the low prevalence of submandibular gland involvement by carcinoma. 5,9 In our study, submandibular gland preservation during treatment of oropharyngeal squamous cell carcinoma was confirmed to be an oncologically sound technique that resulted in no change in disease free survival, disease specific survival, or overall survival compared to gland removal. This is further supported by prior literature reports suggesting that treatment of level 1 during neck dissection for oropharyngeal carcinoma may be unnecessary in the absence of clinical disease.…”
Section: Discussionsupporting
confidence: 57%
“…Several prior reports have suggested the safety of submandibular gland preservation during treatment of head and neck carcinoma, citing the low prevalence of submandibular gland involvement by carcinoma. 5,9 In our study, submandibular gland preservation during treatment of oropharyngeal squamous cell carcinoma was confirmed to be an oncologically sound technique that resulted in no change in disease free survival, disease specific survival, or overall survival compared to gland removal. This is further supported by prior literature reports suggesting that treatment of level 1 during neck dissection for oropharyngeal carcinoma may be unnecessary in the absence of clinical disease.…”
Section: Discussionsupporting
confidence: 57%
“…Similar studies have reported metastasis to submandibular gland from an index tumor in head and neck is either very rare or never found [13][14][15][16]. Fibrous capsule surrounding the submandibular gland provides an effective barrier to the spread of squamous cell carcinoma, even when the gland is compressed by bulky metastatic disease [17].…”
Section: Discussionmentioning
confidence: 84%
“…Baş boyun bölgesindeki primer tümörlerin submandibular beze hematojen yayılma oranı da oldukça düşüktür. Patolojik değerlendirmede de submandibular bezi saran fibröz kapsülün primer baş boyun böl-gesi karsinomlarının yayılmasına engel bir bariyer olarak görev aldığı görülmüştür (5) . Boyunda 1. bölgede gizli lenf nodu tutulumu enderdir.…”
Section: Discussionunclassified